Cloud security: risk factors and security issues in current trends - K.SAI MANOJ, Dr. (International Journal of Engineering and Technology, 2019)
Now a days, cloud computing is an emerging and way of computing in computer science. Cloud computing is a set of resources and services that are offered by the network or internet. Cloud computing extends various computing techniques like grid computing, distributed compu-ting. Today cloud computing is used in both industrial, research and academic field. Cloud facilitates its users by providing virtual resources via internet. As the field of cloud computing is spreading the new techniques are developing. This increase in cloud computing environment also increases security challenges for cloud developers. Users of cloud save their data in the cloud hence the lack of security in cloud can lose the userâ€™s trust.In this paper we will discuss some of the cloud security issues in various aspects like multi-tenancy, elasticity, reliability, availability etc in various sectors, the paper also discuss existing security techniques and approaches for a secure cloud environment. This paper will enable researchers and professionals to know about different security threats and models and tools proposed.Â Â
Keywords: Cloud Computing; Cloud Security; Security Threats; Security Techniques; Cloud Security Standards.